Monetary policy and inequality: An heterogenous agents' approach - Andrea Boitani; Lorenzo Di Domenico; Giorgio Ricchiuti (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2024)
In this paper, we study the impact of contractionary monetary policies on income and wealth inequality. By developing an Agent Based-Stock Flow Consistent model, we show that both the sign and magnitude of monetary policy impacts depend on the heterogeneity characterizing income sources across the population, the composition of households wealth and portfolio preferences, the value of the labor share, and the size of unemployment benefits. Monetary policy can affect inequality through four main transmission channels: saving remuneration, asset prices, aggregate demand and cost-push channels. The paper delivers five main results: i) the impact of monetary policy on income inequality is non-linear and is a function of the degree of symmetry in the distribution of firms and bank shares, markup, and unemployment benefits; ii) the magnitude of the impact is not independent of the inequality measure considered; iii) the short-run effects on wealth inequality due to capital gains and losses (CGL) on long-term bonds are positively correlated with the degree of heterogeneity in the portfolio preferences of households. In the long-run, such effect vanishes. The short-run effect is null in the case of zero heterogeneity; iv) If the monetary shock has an asymmetric impact on portfolio decisions, monetary policy can have a long-lasting impact on wealth inequality through the CGLs in the stock market. In the presence of symmetric shocks, CGLs in the stock market have no effect, neither in the short nor in the long term; v) the higher the labor share, the greater the impact of monetary policy on inequality. Finally, we adopt the income factor decomposition to disentangle how income heterogeneity affect the transmission channels of monetary policies.
Keywords: E4; E52; E53; D31; D63; 330; Monetary policies; income inequality; Agent-Based models; Stock-Flow Consistent models